2001
DOI: 10.1034/j.1601-0825.2001.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the AgNORs, PCNA and ck16 proteins in oral lichen planus lesions

Abstract: The expression of proliferating cell nuclear antigen (PCNA), cytokeratin 16 (ck16) and Ag nucleolar organizer regions (AgNORs) were assessed in 20 cases of lichen planus, 20 cases of keratosis and 20 cases of normal oral mucosa in order to evaluate the rate of keratinocyte proliferation in these tissues. Three hundred cells were counted in each sample: 100 basal cells, 100 suprabasal cells and 100 squamous cells. The mean number of AgNORs and the percentage of PCNA positive cells were calculated. Except from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…PCNA expression were higher in all layers of lichen planus than in both keratosis and normal oral mucosa, it indicates that the keratinocyte proliferation index is higher in lichen planus than in keratosis and normal mucosa. [15] These results were in accordance with our study.…”
Section: Discussionsupporting
confidence: 93%
“…PCNA expression were higher in all layers of lichen planus than in both keratosis and normal oral mucosa, it indicates that the keratinocyte proliferation index is higher in lichen planus than in keratosis and normal mucosa. [15] These results were in accordance with our study.…”
Section: Discussionsupporting
confidence: 93%
“…An increased PCNA expression secondary to inflammation has been reported previously and hence may have led to such a finding in our study. [ 21 22 ] Moreover, PCNA is characterized by a longer half-life (around 20 h) and results in staining of cells which have recently left the cell cycle. [ 23 ] Deregulated expression of PCNA has also been reported in normal tissues and specimens adjacent to tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies[234567891011121314151617181920] included most but not all the parameters as in the present study, providing evidence of variation in anti-VEGF, anti-CD34 and anti-PCNA antibody staining. However, few studies[2345671215181920] have not shown statistically significant results among the parameters considered.…”
Section: Discussionmentioning
confidence: 90%
“…An overall increase in mean scores from normal to OLP, OL, OSF and different grades of OSCC was similar to other studies. [234567891011121314151617181920]…”
Section: Discussionmentioning
confidence: 99%